2013
DOI: 10.1109/lpt.2013.2264456
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 35-nJ Nanosecond Pulse From a Passively Mode-Locked Tm, Ho-Codoped Fiber Laser With Graphene Saturable Absorber

Abstract: We report a passively mode-locked thulium, holmium-codoped fiber laser with graphene saturable absorber. Stable nanosecond pulse with output pulse energy up to 35 nJ is obtained at the repetition rate of 0.964 MHz. The tunable output spectral range is from 1897.69 to 1930.27 nm by simply changing the pump power. Higher output pulse energy is promising but limited by the damage threshold of the fiber component.Index Terms-Graphene saturable absorber, mode-locked fiber laser, thulium doped fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Additionally, researchers from other groups also demonstrated the 2 µm mode‐locked lasers based on WS 2 SA and BP SA, respectively, as shown in Figure d–i. Up to now, 2 µm mode‐locked fiber lasers have been achieved with layered materials, such as graphene, Bi 2 Te 3 , MoS 2 , WS 2 , WTe 2 , WSe 2 , MoTe 2 , and BP, respectively. Among them, several important works should be emphasized, such as the maximum pulse energy of 35.2 nJ, the repetition rate of 58.87 MHz, and the minimum pulse width of 190 fs …”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…Additionally, researchers from other groups also demonstrated the 2 µm mode‐locked lasers based on WS 2 SA and BP SA, respectively, as shown in Figure d–i. Up to now, 2 µm mode‐locked fiber lasers have been achieved with layered materials, such as graphene, Bi 2 Te 3 , MoS 2 , WS 2 , WTe 2 , WSe 2 , MoTe 2 , and BP, respectively. Among them, several important works should be emphasized, such as the maximum pulse energy of 35.2 nJ, the repetition rate of 58.87 MHz, and the minimum pulse width of 190 fs …”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…A different graphene-based mode-locked TDF laser-operating at 1.94 µm in a large anomalous dispersion regime with pulse duration of 3.6 ps and energy of 0.4 nJ was also reported [8]. Recently, Fu et al have reported a passively mode-locked Tm-Ho-codoped fiber laser based on graphene operating with the highest reported pulse energy of up to 35 nJ at 1896.69 nm, however, the peak power was very low due to its long pulse width of over 100 ns [9].…”
Section: Introductionmentioning
confidence: 66%
“…Pulsed Tm 3+ -doped fiber (TDF) lasers operating at 2 µm eye-safe spectral region have attracted substantial attention because of their potential applications in metrology, remote sensing, free-space communication, time-resolved molecular spectroscopy, and mid-IR supercontinuum generation. A number of passively mode-locked TDF lasers have been already reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. They can be roughly divided independently of the operation wavelength into two major categories depending on the mode-locking mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the 2 µm region, there are a few reports about the nanosecond passively mode-locked fiber laser. In 2013, Fu et al realized a passively mode-locked Tm, Ho-codoped fiber laser with a pulse duration of ∼122 ns and pulse energy of ∼35.2 nJ by utilizing graphene as an SA and lengthening the cavity to ∼213 m [22] . Based on NPR and ∼460 m long cavity length, fundamental mode-locked pulses with a pulse duration of ∼304 ns were obtained by Wang et al [23] .…”
Section: Introductionmentioning
confidence: 99%